Mosques without Dome (as a Tourist Attraction): A Religion Journey - Yuke Ardhiati (Catuspata Press, 2022)
Purpose: This research aims to reveal the recent architectonic design phenomena for Indonesian mosques without dome(s) and minarets. All the mosques have potential uniqueness to be tourist attractions. Research methods: The research refers to interdisciplinary methods in qualitative research of four mosques structures without a dome and/or minaret. Findings: Architectonic designs are interpreted as the desire to demonstrate the postmodern architectural spirits (zeitgeist) of the respective architects by performing anti-deterministic, self-sustaining and/or multivalent architecture. Architects do it to provoke to interpret the new interpretations of the Islamic spirit in architecture in an emotional and cognitive way. Implications: The serial of mosques without dome has been potential to be a religion journey. It has also been potential to be tourist attractions.